2010
DOI: 10.1016/j.virol.2010.08.029
|View full text |Cite
|
Sign up to set email alerts
|

UL84-independent replication of human cytomegalovirus strain TB40/E

Abstract: The UL84 gene of human cytomegalovirus is implicated in the initiation of viral DNA replication during lytic infection. UL84 is essential for replication of a cloned viral origin of lytic replication (oriLyt) in vitro and mutants of strains AD169 or Towne with deletions or insertions in UL84 fail to grow in cells permissive for wild type virus. Here we show that UL84 is dispensable for replication of a strain TB40/E clone derived from a bacterial artificial chromosome. The genomes of the fibroblast-adapted str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
1
15
1
Order By: Relevance
“…This contrasts with data from Spector and Yetming (45), who found that UL84 is not required for replication of HCMV strain TB40/E. The discrepancies among these studies remain unresolved.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…This contrasts with data from Spector and Yetming (45), who found that UL84 is not required for replication of HCMV strain TB40/E. The discrepancies among these studies remain unresolved.…”
Section: Discussioncontrasting
confidence: 68%
“…Interaction of UL84 with IE2, via amino acids 68 to 105 of UL84 is necessary to maintain UL84 protein levels in the infected cell (37,38). However, a recent report has indicated that in at least one strain of HCMV (TB40/E), UL84 is not required for viral replication (45).…”
mentioning
confidence: 99%
“…HCMV does not encode a de facto origin binding protein, so the exact mechanism by which it initiates viral lytic DNA replication is unclear. Although, recently, it has been shown that HCMV UL84 can interact with the viral origin of replication and may function as a replication initiator via interactions with C/EBP [38], [48] [49], other work has shown that UL84 is dispensible for HCMV lytic replication [50]. Consequently, we have analysed whether initiation of HCMV DNA replication involves host cell pre-RC factors.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether only the latently infected cells are responsible for the production of these cytokines or whether bystander cells in the population culture are also induced to express these cytokines, we analyzed the expression of cIL-10 and TGF-β in uninfected bystander in the latently infected cells population. CD34 + cells were infected with an isolate of HCMV TB40E (TB40GFP), which expresses GFP under the control of the SV40 origin/promoter cassette (25) and allows expression of GFP in infected undifferentiated myeloid cells (26). Forty-eight hours postinfection, cIL-10 and TGF-β expression was analyzed by intracellular cytokine staining.…”
Section: Intracellular Cytokine Staining Shows That the Latent Secretomementioning
confidence: 99%